Kneser Oscillation Theorem for differential equations with piecewise constant argument - Klaczak, Jerzy (Annales Mathematicae Silesianae, 1991)
In the paper oscillatory properties of solutions of a second order differential equation with piecewise constant argument are studied. In particular, a version of Kneser Oscillation Theorem for such equation is proved.